2012
DOI: 10.1200/jco.2012.42.7161
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for the Management of Fever and Neutropenia in Children With Cancer and/or Undergoing Hematopoietic Stem-Cell Transplantation

Abstract: This guideline represents an evidence-based approach to FN specific to children with cancer. Although some recommendations are similar to adult-based guidelines, there are key distinctions in multiple areas. Implementation will require adaptation to the local context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
322
2
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 322 publications
(341 citation statements)
references
References 133 publications
5
322
2
10
Order By: Relevance
“…Identification of laboratory markers to efficiently and accurately stratify for patients based on risk of serious infectious complication is badly needed in paediatric oncology [14,32]. Our results for PCT and IL-6 are presented by slightly smaller values of sensitivity and specificity than results of abovementioned meta-analysis published by Philips et al or other single studies [4,6,33].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Identification of laboratory markers to efficiently and accurately stratify for patients based on risk of serious infectious complication is badly needed in paediatric oncology [14,32]. Our results for PCT and IL-6 are presented by slightly smaller values of sensitivity and specificity than results of abovementioned meta-analysis published by Philips et al or other single studies [4,6,33].…”
Section: Discussioncontrasting
confidence: 56%
“…In our clinic we start antibiotic therapy in accordance with international 2012 JCO Guideline for management of paediatric febrile neutropenia. We evaluate elements informative for risk stratification included patient-specific factors (including age, malignancy type, and disease status); treatment-specific factors (type and timing of chemotherapy), and episode-specific factors (including height of fever, hypotension, mucositis, blood counts, and available biomarkers -CRP and PCT) [32]. The main criterion for initiating anti-infective therapy remains clinical presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant covariate data including demographic features, age, gender, type of malignancy, phase of chemotherapy, clinical features at presentation, duration of symptoms, initial labarotary findings including total white blood cell (WBC) count, absolute neutrophil count (ANC), and platelet count; radiological findings (if applicable) and microbiological results, management and outcomes were also collected. All patients were treated as inpatients following the "International Pediatric Fever and Neutropenia Guideline" [10].…”
Section: Data Collectionmentioning
confidence: 99%
“…A recent systematic review of randomized control trials in pediatric FN [37] concluded that antipseudomonal penicillin and fourth-generation cephalosporin monotherapy were associated with similar failure and mortality rates as aminoglycoside containing combination therapy. The current recommendations also advise monotherapy as initial empirical antibiotic therapy in pediatric FN [3][4][5][6][7][8][9]. Further, Outpatient management and oral antibiotics were found to be safe in low-risk FN with no infection-related mortality observed in any patient and no significant differences in outcomes compared with inpatient management and intravenous therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed an audit of all hospital admission for pediatric FN during the year 2012 in US [8] revealed that 39% of the discharges had a short length of stay (SLOS) of ≤ 3 days; viral infection and upper respiratory infection comprising the majority with 66.4% of them had no identifiable infections. This has led to the risk based approach and use of intravenous or oral antibiotics in 'low risk' patients [9]. Another important paradigm in the management of pediatric FN is use of antibiotic prophylaxis.…”
Section: Introductionmentioning
confidence: 99%